Depiction of Sex Wars in Closer by Patrick Marber and Dogs Barking by Richard Zajdlic - Hazuková, Barbora (Univerzita Pardubice, 2016)
The aim of this bachelor paper is to depict fights and disputes of heterosexual couples in the plays Closer by Patrick Marber and Dogs Barking by Richard Zajdlic. The first part of the thesis focuses on cultural and historical background of in-yer-face theatre that was developed in the 1990s in Britain. The second part of the work represents a portrayal of modern society and its influence on contemporary heterosexual relationships. The third part offers a thorough analysis of the plays Closer and Dogs Barking. The concluding chapter compares the conflicts between the partners in these dramas.
Zachycení válek pohlaví ve hrách Na Dotek od Patricka Marbera a Pes, který štěká, nekouše od Richarda Zajdlica
Keywords: Closer; Marber, Patrick; Dogs Barking; Zajdlic, Richard; partnerships; sex wars; in-yer-face theatre; Na dotek; Marber, Patrick; Pes, který štěká, nekouše; Zajdlic, Richard; partnerské vztahy; válka pohlaví; "cool drama"